ANTIOXIDANT AND ANTI-INFLAMMATORY POTENTIAL OF DAUCUS CAROTA L. SEED EXTRACTS - M. G. Nabi; A. Latif; K. Ashiq; R. Parveen; S. A. Shah; A. Fiaz; Z. Ramzan (Journal of Animal and Plant Sciences, 2023)
Daucus carota L. is locally known as “Kali Gajar” (black carrot) and is found abundantly in Pakistan. The aim of the current study is to investigate in vitro antioxidant and anti-inflammatory and in vivo anti-inflammatory effects of Daucus carota L. seed extracts. The hot extraction method was used to obtain different extracts. The physiochemical testing, FTIR and mineral content estimation of the seed powder were conducted. UV Visible profiling of the extracts was also done. The in vitro antioxidant activity was performed by using the variety of assays included DPPH, ferric reducing power, hydrogen peroxide scavenging capacity, and phosphomolybdenum test and ascorbic acid was used as a reference. The in vitro anti-inflammatory activity was assessed by inhibition of protein denaturation method and the diclofenac sodium was taken as a standard. The in vivo anti-inflammatory activity was examined by using carrageenan-induced rat paw edema model by taking aspirin as a standard. The results of the UV Visible spectroscopy and FTIR scans showed the presence of various functional groups. The existence of many important primary and secondary metabolites was also confirmed by phytochemical analysis. The physicochemical parameters of seed powder were found to be within the recommended range as stated in USP, 2015. The present study has verified the antioxidant effect of the plant seeds and methanolic extract was found to be more active as compared to the other extracts. The study outcomes have confirmed a significant in vitro inhibition of the protein denaturation and in vivo reduction of carrageenan-induced inflammation in the rat paw. It is concluded that the plant seeds have the potential to reduce inflammation, however toxicological and clinical studies are desired in the future.
Keywords: Daucus carota L.; Black carrot; Medicinal plants; anti-inflammatory; anti-oxidant